Effectiveness of Educational Program on Nurse-midwives’ Knowledge about Pregnancy Induced Hypertension at Bint Al-Huda Hospital in Al-Nasiriya City - Sarah Talb Kadhim1 , Suhad H. Khairi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Pregnancy induced hypertension, is common throughout the world but more frequent in developing countries and cause of maternal and infant mortality and morbidity. Objectives: To the effectiveness of educational program about PIH on nurse-midwives’ knowledge Subjects and Method: A quasi-experimental design, non- probability (purposive) sample of (50) nurse midwives’ who are working in Bint Al-Huda hospital in Al-Nasiriyah City during February 13th through April 2nd 2019. Results: The results of the study show that more than a one third of the study sample are within age group (20-25) years, and had more than a half were married, one third were nursing school graduates and had experiences for 10 years or more. In pretest the nurse’s knowledge show poor and fair level, after intervention of the program and through two posttest in different timing the score show a progress in result to very good level. (84.9%) for knowledge during posttest I and to (100%) for posttest II to knowledge. Conclusion: The study concludes there were significant of educational program on nurse-midwives’ knowledge.